The Study of Flow Resulting from Wave on Lhonga Beach, Aceh Besar - Muhammad Irham; Ichsan Setiawan (Journal Omni-Akuatika, 2017)
Dynamic interaction between waves and topographic generate flow dynamics that affect Lhonga coast, Aceh Besar. To analyze the dynamics, the numerical model of currents induced by wave was developed with the explicit finite difference approach method. The model in this study was tested by verifying the result directly with the field data obtained previously. The model is applied in Lhoknga coast of Aceh Besar district with the aim to study how the dynamics of hydro-oceanography as one of the elements to support the preservation of the marine resources of the area. Based on the simulation, the results obtained that the wave occurred in Lhoknga beach relatively small with the dominant direction to the northwest and the maximum of wave height occurs during the high tide condition. The result also informed that the distribution of longshore currents is generally moving from west to east along the coast. The direction of dominant current occurs in the area of 10-15 meters from the shore with an average depth of 6 meters. Keywords: wave flow, flow dynamics, beach, hydro-oceanography